Pyridinyl Functionalized MCM-48 Supported Highly Active Heterogeneous Palladium Catalyst for Crosscoupling Reactions - Sarkar, Shaheen M.; Lutfor, M. R.; M. M., Yusoff (Royal Society of Chemistry, 2015)
An MCM-48 supported 2-pyridinylmethanimine Pd-catalyst was found to be a highly efficient catalyst in the Mizoroki–Heck, Suzuki–Miyaura and copper-free Sonogashira cross-coupling reactions of aryl halides under aqueous reaction conditions. The catalyst efficiently promoted these coupling reactions with ppm levels of palladium to afford the corresponding coupling products in up to 98% yield. The supported Pdcatalyst was readily recovered and reused several times without significant loss of its catalytic activity.